Keys of the female political citizenship in the first half of the twentieth century in Argentina - Valobra, Adriana María (2016)
In this article, we explores some facts that marked the construction of Argentina as a nation in the first half of XX centruy. From a gender perspective, we examines changes and continuities in the construction of female political citizenship. We highlights the compulsory obligations presented in differents laws and institutions associated with masculinity and femininity social practices. In this way, the central problem is linked with the definition of women as subjects and individual.